A implantação da reforma do ensino médio e a organização do trabalho pedagógico em uma escola de Minas Gerais: diretrizes e práticas - Barbosa, Beatriz Menezes (2019)
This Master’s dissertation is inserted in the line of research “State, Politics and Education Management” on the curriculum reform in High School Education. It is a study on the implementation of the High School Education Reform according to the Brazilian Federal Law 13.415/2017 in the state of Minas Gerais based on guidelines of the Secretariat of Education of Minas Gerais (SEE/MG). Several questions emerged regarding this reform; however, our focus is on how this reform is being implemented in Minas Gerais. Under this perspective, the following questions should be answered: What are the guidelines for the Pedagogical Work Organization in the schools, which will implement the reforms? What are the concepts of education and student training present in the guidance documents? The general aim of this research is to analyse the guidelines of the Secretariat of Education of Minas Gerais (SEE/MG) for the implementation of the High School Education reform, carried out by means of the Brazilian Federal Law 13.415/2017 in schools in the state of Minas Gerais. In order to achieve our aims, we searched alternatives through the following specific objectives: analyze the educational politics for High School Education , based on the Brazilian Federal 1988 Constitution until the coup d'état of 2016; present and analyze the High School Education reform regulated by the Brazilian Federal Law 13.415/2017, and the context of its implementation; understand the principles and concepts of the pedagogical work in schools; collect and analyze documents that guide the pedagogical work on High School Education in schools in Minas Gerais, according to the Brazilian Law 13.415/2017; understand and analyze the process of legislation and implementation of the High School reform in the state of Minas Gerais, based on guidelines of the Secretariat of Education of Minas Gerais (SEE/MG), sent to the state-owned schools of Minas Gerais; identify and discuss how effective pedagogical work organization is in state-owned schools of Minas Gerais, concerning the guidelines to implement the High School Education curriculum reform. In order to achieve this purpose, a methodological qualitative approach research was conducted, besides some document analysis of the guidelines and legislation used for the organization of the pedagogical work. This bibliographic research was based on Dourado (2007), Freire (2000), Freitas (2008) (2015) (2018) (2019), Frigotto (2018), Krawczyk (1999) (2011) (2014), Oliveira (2010), among others, aiming at training on critical thinking, an education seen as a way to achieve citizenship. Data reveal the legislation on High School Education Reform changes the curriculum under a market perspective, according to the neoliberal system in which education aims at the job market.